2014
DOI: 10.1080/13607863.2014.962007
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among perceived discrimination, self-perceptions of aging, and depressive symptoms: a longitudinal examination of age discrimination

Abstract: Findings demonstrate the importance of recognizing perceived discrimination and negative self-perceptions of aging as well as how the negative effects of age discrimination on self-perceptions of aging can be risk factors for the development of depressive symptoms in late life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
69
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 38 publications
7
69
2
5
Order By: Relevance
“…Three studies examined SPA as a mediator between personality or social characteristics and depressive symptoms, all using longitudinal data from the US Health and Retirement Study (HRS). Han and Richardson found that participants who reported more age discrimination had lower SPA 4 years later, which predicted worse depressive symptoms at the second time point. Kwak and colleagues reported that older adults who reported receiving more care in 2006 reported lower SPA in 2008 and worse depressive symptoms in 2010, with SPA as a partial mediator.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Three studies examined SPA as a mediator between personality or social characteristics and depressive symptoms, all using longitudinal data from the US Health and Retirement Study (HRS). Han and Richardson found that participants who reported more age discrimination had lower SPA 4 years later, which predicted worse depressive symptoms at the second time point. Kwak and colleagues reported that older adults who reported receiving more care in 2006 reported lower SPA in 2008 and worse depressive symptoms in 2010, with SPA as a partial mediator.…”
Section: Introductionmentioning
confidence: 98%
“…14 In addition to living longer and being physically healthier, older adults with positive SPA have fewer depressive symptoms. [15][16][17][18] In addition to being the most disabling condition worldwide, 19 depressive symptoms lead to other deleterious outcomes in later life, including suicide and all-cause mortality, and may in fact contribute to the poorer health behaviors and health outcomes 20 seen in older adults with negative SPA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few recent studies that have examined perceived discrimination longitudinally have found inconsistent results; some have found decreases in perceived discrimination from adolescence to emerging adulthood (Huynh & Fuligni, 2012), whereas others have found interpersonal variation in the trajectories of perceived discrimination (Hunte, 2011; Kam et al, 2010), and that increases in perceived discrimination are associated with substance use (Kam et al, 2010), depressive symptoms (Han & Richardson, 2015; Schulz et al, 2006), and obesity (Hunte, 2011). Other studies (Hurd et al, 2014) have found that initial levels of perceived discrimination, but not changes in discrimination over time, predict anxiety, depression, and alcohol use.…”
mentioning
confidence: 99%
“…Проблемы их преодо-ления на рынках являются предметом ряда иссле-дований зарубежных и отечественных специали-стов [1][2][3][4][5][6][7][8].…”
unclassified